INOVASI NASI MENJADI KERUPUK YANG DISUKAI KONSUMEN - N.R, Muh. Aqil Maulana; Andini, Putri; Riani, Nengsi; Bahrum, Sulpiani; Salmiati, Salmiati; Sapar, Sapar; Abbas, Estria Indrawati (PT Naureen Digital Education, 2024)
Utilizing Rice into Creative and Marketable Food Products. The goal of the student creativity program-entrepreneurship (PKM-K) is to motivate students to engage in entrepreneurship by managing rice into marketable food products. Rice is highly beneficial for health, including brain health, being the main energy source for the body, and boosting the immune system. This rice cracker product can also enhance creativity for an entrepreneur, making consumers interested in purchasing the rice crackers. The method of implementing this program includes input, process (production), output, and evaluation. The results of this program are input, conducting market surveys to understand market conditions. Next is the feasibility study of the business to be run. The final stage is selecting materials and providing the place, as well as facilities and infrastructure to support the production process. Process (production), the process of making rice crackers, from preparation of materials and tools to rice crackers ready for sale. Output, which is the result of creative rice crackers ready to be consumed and marketed to consumers. Lastly, the evaluation, this stage is carried out after the production of the rice cracker product is completed. At this stage, we will review the shortcomings that make consumers dissatisfied with our product. The conclusion of the PKM-K program utilizing rice into marketable rice cracker food products can provide students with the skills to remain innovative and creative in processing rice, give students the opportunity to practice entrepreneurship with a comprehensive understanding of entrepreneurial concepts, and build the spirit of students to continue doing business.